2003
DOI: 10.1177/014572170302900612
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Problem Solving and Diabetes Control in Type 2 Diabetes Self-Management

Abstract: The problem-solving model may help identify ineffective problem-solving patterns in persons with poor diabetes control. Empirical studies testing the model are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 17 publications
2
45
0
3
Order By: Relevance
“…Despite the identification of many factors, 430497Q HRXXX10.1177/10497323114304 97Audulv et alQualitative Health Research 1 Mid Sweden University, Sundsvall, Sweden the underlying mechanisms by which these factors influence self-management have not been well explored. For example, Hill-Briggs, Cooper, Loman, Brancati, and Cooper (2003) found that people experienced problems integrating diabetes self-management into their lives. The participants in their study found it difficult to maintain a healthy diet or integrate medication into their daily schedule.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the identification of many factors, 430497Q HRXXX10.1177/10497323114304 97Audulv et alQualitative Health Research 1 Mid Sweden University, Sundsvall, Sweden the underlying mechanisms by which these factors influence self-management have not been well explored. For example, Hill-Briggs, Cooper, Loman, Brancati, and Cooper (2003) found that people experienced problems integrating diabetes self-management into their lives. The participants in their study found it difficult to maintain a healthy diet or integrate medication into their daily schedule.…”
Section: Introductionmentioning
confidence: 99%
“…The few recorded comments of these family members were excluded from analyses. Table I shows that the community sample was fairly heterogeneous in terms of their sex and marital status, although many participants possessed higher composite co-morbidity and diabetes severity levels than other published samples, [9,17] were obese, and received over 12 prescribed medications. The majority of participants were also retired and/or had lower than national average income levels and received healthcare services under Medicare or Medicaid insurance coverage.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5]8,9,16,25] The contributing factors leading to this type of patient perception requires further investigation to inform the design of more feasible SDM diabetes management interventions for many settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the individual level, external locus of control, delayed intellectual and emotional development, impulsive and avoidant coping styles, and number of life events have been associated with poorer metabolic control [8][9][10].…”
Section: Introductionmentioning
confidence: 99%